METODE PENURUNAN RESPON DINAMIK SISTEM POROS-ROTOR DENGAN PEREDAM VISCOUS ROTARY - Nusyirwan Nusyirwan (Jurnal Ilmiah Teknik Mesin POROS, 2014)
Abstract: Viscosity or viscosity is one of the quantities that are very important in the analysis of the behavior and movement of fluids that come into contact with other objects such as solids {solid body). Viscous dampers can be used to reduce the amplitude of the response due to the unbalanced mass, rotation critically, noise and shock loads. Absorbers working with fluid film bearing securities which are placed at a certain point, which is connected to the shaft-rotating rotor. Certain viscosity fluid will be forced to pass through a narrow slit with a certain pressure that can absorb the energy supplied by the shaft, this damping effects that can provide resistance to the rotor shaft system because the fluid has a linear damping and damping effect histeriktik. Viscous dampers can be used to reduce vibration amplitude response at a fixed price in accordance with the physical nature of the damper, the use of viscous dampers are widely used to control engine speed and turbine rotational speeds are like a helicopter rotor. From the test we can produce the damping effect on the engine rotation can reduce the response time domain vibration with an amplitude reduction of approximately 60% for the damping ratio ζ = 0.5.